EDUKASI DETEKSI DINI DAN PENCEGAHAN DIABATES MELITUS - AR, Dwi; Sulayfiah, Tri Nili; Wahyuni, Ida (Jurnal LENTERA, 2025)
The current high consumption of sweetened beverages and foods has contributed to the high mortality and morbidity rates caused by overweight and obesity, as well as non-communicable diseases such as diabetes mellitus and cardiovascular disease. This situation is a global concern. Excessive consumption of sweetened foods and drinks has become a serious health problem. Furthermore, various complications resulting from uncontrolled high blood sugar levels also pose a serious challenge because they can lead to various comorbidities. Therefore, the public urgently needs clear and adequate information and knowledge on how to prevent diabetes mellitus, including how to maintain normal blood glucose levels. This community service aims to reduce the incidence of DM in general, and make the public more aware of its dangers through education on early detection and prevention of DM. This method uses counseling on health education or education on DM prevention and its prevention. This includes patient screening, PowerPoint presentations, and leaflets. Community participation is documented and evaluated to assess their knowledge of diabetes. This activity results in increased knowledge after the counseling. So this activity can be a solution and intervention option to improve the quality of people's lives with adequate knowledge